Monte Carlo Simulation to Test the Effectiveness of Crystal Detector Length for PHITS-Based PET Modality - Urfa, Gusti Atika; Sari, Nurma; Wianto, Totok; Wahyono, Sri C; Fahrudin, Arfan E; Nasrulloh, Amar V (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
PET (Positron-emission tomography) is used to determine physiological and metabolic functions in the body. Monte Carlo simulation is an important part of PET imaging, and the Particle Heavy Ion Transport code System (PHITS) is a simulation platform that can be used to perform Monte Carlo simulations. This study uses a Monte Carlo simulation based on PHITS to determine the range of gamma absorption with an energy of 511 keV in a scintillation detector crystal material. The gamma absorption range determines the effective crystal length in the PET modality. The simulation process is carried out by shooting Gamma at various types of materials, which are the materials used in PET scintillation crystals. The materials used in this simulation are NaI (Sodium Iodide), BaF2 (Barium Florida), BGO (Bismuth Germanate), and GSO (Gadolinium Oxyorthosilicate), considering their atomic number and crystal density. The crystal material is capable of absorbing gamma radiation with an energy of 511 keV with detailed crystal lengths for each NaI crystal of 0.26 cm; 0.25 cm BaF2 crystals; 0.1cm BGO crystals; and 0.18 cm GSO crystals. The crystal length from this simulation is smaller than the commercially available crystal length (range 1-3 cm). Based on the crystal length data, the most effective crystal for absorbing gamma radiation is the BGO crystal.